ANALISIS PERSEPSI WISATAWAN TERHADAP PENERAPAN KONSEP PARIWISATA RAMAH MUSLIM (PRM) DI TAMAN WISATA CIBODAS - Ramdani, Dadan (JURNAL MATA PARIWISATA, 2025)
Cibodas Tourism Park is a popular natural tourist destination in West Java with the potential to develop the Muslim-Friendly Tourism (MWT) concept, given the high number of Muslim tourists visiting. However, the destination currently lacks official MWT certification, necessitating a study to determine the level of implementation of the concept based on tourist perceptions. This study aims to analyse the implementation of MWT across four main dimensions: accessibility, communication, supporting environment, and services, and to measure their significance against the neutral category standard. The research method used was a descriptive quantitative approach, with data collected through questionnaires from 100 tourist respondents. Data were analysed using a one-sample t-test with a benchmark value of 3 (the "sufficient" category). The results showed that the overall average score of tourists' perceptions of MWT at Cibodas Tourism Park was 3.98, with a significance value <0.05, significantly above the neutral category. Specifically, the accessibility dimension scored 4.02; communication 3.95; supporting environment 3.91; and service 4.05. These data indicate that the available facilities and services are sufficient to accommodate the needs of Muslim tourists, although improvements are still needed in terms of promotion, the addition of halal facilities, and the strengthening of tourism information. These findings indicate that Cibodas Tourism Park has significant potential to be developed as a leading Muslim-Friendly Tourism destination in West Java.